2020
DOI: 10.3390/genes11040416
|View full text |Cite
|
Sign up to set email alerts
|

Turtle Insights into the Evolution of the Reptilian Karyotype and the Genomic Architecture of Sex Determination

Abstract: Sex chromosome evolution remains an evolutionary puzzle despite its importance in understanding sexual development and genome evolution. The seemingly random distribution of sex-determining systems in reptiles offers a unique opportunity to study sex chromosome evolution not afforded by mammals or birds. These reptilian systems derive from multiple transitions in sex determination, some independent, some convergent, that lead to the birth and death of sex chromosomes in various lineages. Here we focus on turtl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 107 publications
(230 reference statements)
3
50
0
Order By: Relevance
“…Our data expanded the physical mapping of genes involved in sexual development by detecting 20 genes out of 32 core genes in the vertebrate sex determination/differentiation cascade, including 10 genes previously reported [ 10 , 12 ]. Our findings strengthen the notion that sex chromosomes have followed independent evolutionary trajectories in distinct turtle lineages [ 43 ], as have turtle and avian sex chromosomes, and uncovered sex-linked and autosomal intra- and inter-chromosomal rearrangements. For instance, we confirmed that C. picta CPI-7 is homologous to red-eared slider ( T. scripta ) chromosome 6 [ 35 ] ( Figure 3 ), and to chicken Z chromosome ( Figure 4 B) [ 5 , 12 ], which in turn, is also homologous to the Mexican giant musk turtle ( Staurotypus triporcatus ) XY sex chromosomes [ 21 , 44 ], and to chromosome 6 of the softshell turtles Apalone spinifera and Pelodiscus sinensis [ 36 , 45 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our data expanded the physical mapping of genes involved in sexual development by detecting 20 genes out of 32 core genes in the vertebrate sex determination/differentiation cascade, including 10 genes previously reported [ 10 , 12 ]. Our findings strengthen the notion that sex chromosomes have followed independent evolutionary trajectories in distinct turtle lineages [ 43 ], as have turtle and avian sex chromosomes, and uncovered sex-linked and autosomal intra- and inter-chromosomal rearrangements. For instance, we confirmed that C. picta CPI-7 is homologous to red-eared slider ( T. scripta ) chromosome 6 [ 35 ] ( Figure 3 ), and to chicken Z chromosome ( Figure 4 B) [ 5 , 12 ], which in turn, is also homologous to the Mexican giant musk turtle ( Staurotypus triporcatus ) XY sex chromosomes [ 21 , 44 ], and to chromosome 6 of the softshell turtles Apalone spinifera and Pelodiscus sinensis [ 36 , 45 ].…”
Section: Discussionsupporting
confidence: 87%
“…CMA 3 staining in Emys trinacris ( Figure 3 g) showed GC content localized in the centromere and telomere in some chromosomes, in accordance with a previous report in T. s. elegans [ 53 ]. Additionally, it was previously shown that the chromosomes that carry the genes of the nucleolar organizing region (NOR) vary in the degree of heteromorphy and often correspond to the sex chromosomes in turtles [ 22 , 55 ]. Despite evidence from molecular phylogenetic studies that show differences between E. trinacris and E. orbicularis [ 13 , 56 ], our cytogenetic comparative analysis revealed similarity between the two species.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, as revealed here in our study, even with ancient origin, they can also be found practically intact in recent lineages, where the X and Y of R. rufipes are undistinguished from each other, with the Y sex chromosome being identified solely by comparative genomic hybridization and recruitment of several SSR motifs. The sex chromosomes may remain undifferentiated for many reasons, for example, transitions and turnovers involving XY and ZW, evolutionary advantages promoted by the recombination between XY and/or Z and W, as well as shifts involving autosomes [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , …”
Section: Discussionmentioning
confidence: 99%